Smooth Trajectory Planning for Robot under Multiple Constraint - Liu Jing; Zhang Ming (Jixie chuandong)
Due to the restriction of the motor parameter,the various constraints,such as angular velocity constraint and angular acceleration constraint should be considered when planning the trajectories of robot. By analyzing the constraints condition,a novel smooth and time optimal trajectory planning approach is proposed based on parametric modified trapezoidal. The time optimal trajectory planning problem which consider kinematics and dynamics constraints are transformed into a two-variable optimization problem with above trajectory planning approach,the time optimal trajectory is obtained by genetic algorithm. The effectiveness of the planning algorithm is verified by an experiment for a two degree hybrid manipulator. The results show that this planning algorithm can make full use of driving performances,and guarantee the continuity of the joint acceleration and torque.